Long acting somatostatin treatment of paraneoplastic Cushing's syndrome in a case of Zollinger-Ellison syndrome. Issue 6 (June 1988) - Ruszniewski, P; Girard, F; Benamouzig, R; Mignon, M; Bonfils, S
Abstract : Cushing's syndrome, caused by ectopic ACTH production during Zollinger-Ellison syndrome, raises difficult therapeutic problems. We report a case of clinical and biological efficacy of long acting somatostatin (SMS) in this condition. In a short term study with 200 micrograms SMS bid, symptoms of hypercorticism disappeared while cortisol and ACTH serum concentrations fell below the normal values. Longterm treatment was instituted with 50 micrograms SMS bid. Excellent clinical efficacy as well as normal cortisol and ACTH serum concentrations were maintained during the nine month follow up. Lipotrophic hormone (LPH) serum concentration remained raised. No decrease in size of hepatic metastases was observed. Long acting somatostatin analogues may be useful in endocrine paraneoplastic syndromes.